2008
DOI: 10.1158/0008-5472.can-07-2491
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Switching of Human Melanoma Cells between Proliferative and Invasive States

Abstract: Metastatic melanoma represents a complex and heterogeneous disease for which there are no therapies to improve patient survival. Recent expression profiling of melanoma cell lines identified two transcription signatures, respectively, corresponding with proliferative and invasive cellular phenotypes. A model derived from these findings predicts that in vivo melanoma cells may switch between these states. Here, DNA microarray-characterized cell lines were subjected to in vitro characterization before s.c. injec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

56
795
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 672 publications
(879 citation statements)
references
References 40 publications
56
795
1
4
Order By: Relevance
“…This was also in agreement with observations that showed increased expression of MITF in MM (Gray-Schopfer et al, 2007). In addition, BCSC-1 overexpression in Mewo cells decreased MITF expression (Table S1) (low MITF levels) phenotype (Hoek et al, 2008a). Our gene expression studies in Mewo cells showed that BCSC-1 overexpression decreased MITF mRNA levels (Table S1).…”
Section: Significancesupporting
confidence: 91%
“…This was also in agreement with observations that showed increased expression of MITF in MM (Gray-Schopfer et al, 2007). In addition, BCSC-1 overexpression in Mewo cells decreased MITF expression (Table S1) (low MITF levels) phenotype (Hoek et al, 2008a). Our gene expression studies in Mewo cells showed that BCSC-1 overexpression decreased MITF mRNA levels (Table S1).…”
Section: Significancesupporting
confidence: 91%
“…Although our study confirms that predicting non-SLN positivity on the basis of SLN tumour load is unreliable, it demonstrates that SLN tumour burden has an impact on DFS. Recent experimental studies using melanoma cell lines in mice have impressively shown that melanoma cells can switch their transcriptional profile from an invasive migrating one to a proliferative profile associated with melanocytic differentiation (Hoek et al, 2008). We hypothesise that the evaluation of the invasive markers in melanoma metastases might improve the predictive accuracy of the SN status.…”
Section: Discussionmentioning
confidence: 93%
“…[20][21][22]. However, direct measurements of MITF during melanoma progression by ourselves and others (23)(24)(25) suggest that MITF is more commonly down-regulated in advanced melanoma.…”
Section: Discussionmentioning
confidence: 99%